234k views
2 votes
Help I don’t understand this one :/

Help I don’t understand this one :/-example-1
User Cama
by
4.8k points

2 Answers

4 votes

Answer:

x = 24.

Explanation:

Set 96 = (x+2)+(x+2) + (x-2)+(x-2). Then simplify: 96 = (2x+4) + (2x-4). Simplify again XD: 96 = 4x (since +4 and -4 cancel out to get 0) . Divide 96 by 4 and your final answer should be 24 Wow..that was pretty slight lol :D

User Nate Vaughan
by
5.3k points
3 votes

Okay I’ll give it my best to explain and solve understand I’m human and if I get this wrong I made a mistake please don’t hate me having said that 96= {x+2} * {x-2} combining like terms x*x (2-2=0) = 92 x^2 and that’s how far I can get you

User Doctorer
by
4.7k points